Generation and comparison of CRISPR-Cas9 and Cre-mediated genetically engineered mouse models of sarcoma - Jianguo Huang (Nature Portfolio, 2017)
Site-specific recombination and CRISPR-Cas9 have been used to generate genetically engineered mouse models of cancer. Here the authors compare sarcomas generated using both systems and see similar genetic and cellular phenotypes, suggesting CRISPR-Cas9 can be used to rapidly generate sarcoma models.